(untitled) (Journal of Educational Sciences, 2018)
The article considers the changes in hematological and functional indicators in students during the examination session. To assess the possible occurrence of violations of students ‘health status, ascertaining the level of the price of adaptation when influencing the students’ body of university loads, the most informative indicators are determined. In terms of leukocyte status, 45% of students who have leukocyte counts within the reference values of the norm have a successful adaptation reaction corresponding to their health. When comparing hematological indicators and health indicators, the most unfavorable values were found in the form of elevated glucose, increased systolic pressure, and an increase in lymphocyte count. An increase in the lymphocyte count is considered as one of the indicators of unfavorable adaptation to higher education. At 33%, the average level of stress was found, 67% showed a low level of stress, which indicates a state of psychological adaptation to workloads. Adaptation of students to study conditions in higher education is a complex multi-level physiological process. The development of disadaptation during the training period can have a negative impact on the functional state of the organism and lead to the development of pathological processes. Key words: study load, students, lymphocyte, monocyte, adaptation.